DESIGN OF POINT OF SALE INFORMATION SYSTEM CASE STUDY: MAJU JAYA GROCERY STORE - Achmad Amirudin; Rohman Dijaya; Hamzah Setiawan; Arif Senja Fitrani (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to design and implement a Point of Sale (POS) system as a technological solution to enhance sales transaction efficiency, inventory management, and customer data processing in retail and service-oriented businesses. Method: The research adopts a software engineering approach, encompassing user requirements analysis, interface design, and system testing to ensure the application meets user and operational needs. The system integrates payment processing, receipt generation, and real-time sales recording within a unified platform, while also supporting cloud connectivity and cashless transactions to align with modern digital practices. Results: The implementation of the POS system demonstrated improvements in service speed, accuracy of transaction recording, and overall customer satisfaction. Novelty: This study provides an applicable model for developing integrated, cloud-connected POS systems, emphasizing the role of digital transformation in enhancing business performance and operational reliability in the retail sector.